2003
DOI: 10.1038/sj.onc.1207281
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis signaling triggered by the marine alkaloid ascididemin is routed via caspase-2 and JNK to mitochondria

Abstract: The marine alkaloid ascididemin (ASC) was shown to exert cytotoxicity even against multidrug-resistant cancer cells. Here, we address the signaling pathways utilized by ASC to trigger apoptosis in Jurkat leukemia T cells. We show that ASC (0.5-20 lM) induces a mitochondrial pathway that requires the activation of the initiator caspase-2 upstream of mitochondria. ASC-triggered apoptosis occurred independent of CD95, but required mitochondrial dysfunction. The activation of caspase-2 was shown to precede the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Numerous reports in the literature point to DNA damage as a trigger for apoptosis (Norbury and Zhivotovsky, 2004), which would be consistent with the results of this study. Caspase-2 has been suggested as a signal linking drug-induced DNA damage and mitochondrial dysfunction leading to downstream apoptotic events including caspase-3 activation (Lassus et al, 2002;Dirsch et al, 2004;Robertson et al, 2004). Our data demonstrate that RH1 treatment induced caspase-3 cleavage in NQ16 cells, suggesting a caspase-3-dependent route of RH1-induced apoptosis.…”
Section: In Vitro Toxicity Of Rh1 775supporting
confidence: 54%
“…Numerous reports in the literature point to DNA damage as a trigger for apoptosis (Norbury and Zhivotovsky, 2004), which would be consistent with the results of this study. Caspase-2 has been suggested as a signal linking drug-induced DNA damage and mitochondrial dysfunction leading to downstream apoptotic events including caspase-3 activation (Lassus et al, 2002;Dirsch et al, 2004;Robertson et al, 2004). Our data demonstrate that RH1 treatment induced caspase-3 cleavage in NQ16 cells, suggesting a caspase-3-dependent route of RH1-induced apoptosis.…”
Section: In Vitro Toxicity Of Rh1 775supporting
confidence: 54%
“…A recent report (39) showed that both caspase-2 and caspase-8 are activated in HOXA5-induced apoptosis of breast cancer cells, yet the sequential activation of these two caspases was not demonstrated. Another study showed that the marine alkaloid ascididemin induces Jurkat T cell apoptosis that requires caspase-2 activation upstream of mitochondria and caspase-8 activation as an effector caspase downstream of mitochondria (40). The present study is, to our knowledge, the first to show that caspase-2 may act upstream of caspase-8 before mitochondrial damage.…”
Section: Resultsmentioning
confidence: 56%
“…Notably, while both CTAR1 and CTAR2 are known to activate the NF B axis, CTAR2 alone engages the c-Jun N-terminal kinase (JNK) pathway. 36 Of considerable interest, a recent publication 39 that appeared during the writing of this article has provided evidence that apoptosis signaling triggered by the marine alkaloid, ascididemin (ASC), is dependent on JNK activation upstream of caspase-2; caspase-2, in turn, was shown to link the DNA-damaging activity of ASC to downstream mitochondrial perturbation. Moreover, Debatin et al have shown that inhibition of JNK activity delays the onset of apoptosis induced by cellular stress (including cisplatin and doxorubicin) in a Jurkat T cell model.…”
Section: Discussionmentioning
confidence: 99%